124k views
1 vote
Pls help need answer ASAP 100 POINTS TO ANSWER I WILL REPORT U IF U ANSWER FOR ONLY POINTS

Pls help need answer ASAP 100 POINTS TO ANSWER I WILL REPORT U IF U ANSWER FOR ONLY-example-1
User Whiteatom
by
6.6k points

2 Answers

2 votes

Answer:

Your answer is Number 3

Explanation:


(2x-3)^(2) =\\(2x-3)(2x-3)=\\4x^(2) -6x-6x+9=\\4x^(2)-12x+9\\5x^(2)-(4x^(2)-12x+9)\\ -12x+9\\5x^(2)-(4x^(2)-12x+9)\\</p><p> 5x^(2) -4x^(2) +12x-9=\\</p><p>x^(2)+12x-9\\

User Vadim Khotilovich
by
6.8k points
6 votes

Answer:

3 x^2 +12x-9

Explanation:

5x^2 - (2x-3)^2

We need to FOIL the second term

(2x-3)^2 = (2x-3) (2x-3) = 4x^2 -6x-6x+9 = 4x^2 -12x+9

Replacing it in to the original equation

5x^2 - (4x^2 -12x+9)

Distribute the minus sign

5x^2 - 4x^2 +12x-9

Combine like terms

x^2 +12x-9

User Onyambu
by
5.4k points